Bilateral comparison of anterior shoulder position in elite tennis players - Ellenbecker, T.; Roetert, E. P.; Petracek, K.; Kovacs, M.; Barajas, N.; Bailie, D. (International Journal of Sports Physical Therapy, 2022)
Background: In elite tennis players, musculoskeletal adaptations in the dominant upper extremity have been reported for range of motion, strength, and scapular biomechanics. In addition to scapular dysfunction, tightness and inflexibility of the pectoral musculature have been identified as risk factors for the development of overuse shoulder injury in overhead athletes. Hypothesis: Differences in anterior shoulder position will be identified between the dominant and non-dominant extremity in elite tennis players. The purpose of this study was to examine bilateral differences in anterior shoulder posture measured using a double square in elite tennis players without shoulder injury. Study Design: Descriptive Laboratory Study Methods: Three hundred and six uninjured elite tennis players were measured in the supine position using a double square method to measure anterior shoulder position. The distance from the surface of the table to the anterior most position of the shoulder (in millimeters) was measured bilaterally and compared. A dependent t-test was used to test for significant differences in anterior shoulder position between the dominant and non-dominant extremity. Results: One hundred thirty-three males and 173 females were included in this study with a mean age of 16.58 years. The mean difference between extremities indicates increased anterior shoulder positioning on the dominant shoulder of 7.65 mm in females, and 8.72 in males. Significantly greater (p<.001) anterior shoulder position measures were documented on the dominant shoulder as compared to the non-dominant shoulder. Conclusions: The results of this study showed significantly (p<.001) greater anterior shoulder position on the dominant extremity of elite male and female tennis players. The differences of 7-8mm between extremities has clinical application for interpreting anterior shoulder position test results in this population.